Interculturality in intercultural education policy (2015)
This reflection paper reconstructs the normative contents for the concept of multiculturalism in order to clearly differentiate it from affirmative action. It aims at providing normative criteria for assessing current policies and designing some that conform to the ideals of multiculturalism. Accordingly, a conceptual analysis based on the comparison between multicultural affirmative action and intercultural policies is made. In the first part, the problems of intercultural education understood as an affirmative action are discussed, the second part proposes some normative criteria to support intercultural education policies that promote the values of Latin American interculturalism: justice, equality, respect, dialogue, and mutual learning between cultures. The main results highlight that educational policies based on affirmative action may lead to the assimilation of cultures subalternized by the dominant ones, or even encourage isolation between them, meanwhile intercultural education policies promote dialogue, respect, and coexistence between cultures in a context of equality.